2001
DOI: 10.1111/j.1439-0418.2001.00496.x
|View full text |Cite
|
Sign up to set email alerts
|

Host‐size‐dependent feeding behaviour and progeny sex ratio of Anisopteromalus calandrae (Hym., Pteromalidae)

Abstract: Host-size related feeding and oviposition behaviour, and allocation of progeny sex by Anisopteromalus calandrae (Howard) were tested on Sitophilus oryzae L. The parasitoid showed a host-size-dependent partition of feeding and oviposition behaviour, preferring small hosts for feeding, but large hosts for oviposition. Neither the mutual interference nor the host density showed any eect on the behaviour of the parasitoid. Allocation of progeny sex by the female parasitoid appeared to be based more likely on absol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The parasitoid density and length of exposure to the host may affect the successful of parasitism (Sagarra et al 2000, da Silva-Torres et al 2010, progeny production (Chong and Oetting 2006), offspring sex ratio (Choi et al 2001), life cycle length (egg to adult; Barbosa et al 2008Barbosa et al , 2010, and adult longevity in T. howardi. Thus, adequate parasitoid densities per host and exposure times can enhance the quality and number of individuals produced.…”
mentioning
confidence: 99%
“…The parasitoid density and length of exposure to the host may affect the successful of parasitism (Sagarra et al 2000, da Silva-Torres et al 2010, progeny production (Chong and Oetting 2006), offspring sex ratio (Choi et al 2001), life cycle length (egg to adult; Barbosa et al 2008Barbosa et al , 2010, and adult longevity in T. howardi. Thus, adequate parasitoid densities per host and exposure times can enhance the quality and number of individuals produced.…”
mentioning
confidence: 99%
“…The density of parasitoids per host affects the parasitoid offspring (Thomazini andBerti Filho 2000, Matos Neto et al 2004), the sex ratio (Choi et al 2001), the parasitism capacity (Sampaio et al 2001), the duration of the life cycle, the size of the body, and the longevity of the imagines (Silva-Torres and Matthews 2003). To minimize the cost and labor and to maximize the production of parasitoids in mass rearing programs, it is, therefore, necessary to study the density of the parasitoids in relation to the host (Sagarra et al 2000a).…”
Section: Introductionmentioning
confidence: 99%
“…The highest number of eggs was laid on the larvae with tunnel diameter of 1.6 mm and the lowest was seen in pupae and small larvae. Choi et al (2001) also reported that A. calandrae preferred to lay eggs on relatively large S. oryzae larvae.…”
Section: Resultsmentioning
confidence: 99%
“…Visarathanonth et al (2010) investigated the egg laying duration of A. calandrae parasitizing S. zeamais fed with milled rice. Several authors determined the ovipositional preference of the parasitoid on different sizes of hosts (Choi et al, 2001;Smith, 1993).…”
Section: Introductionmentioning
confidence: 99%